THE PHYSICOCHEMICAL, OXIDATIVE AND TEXTURAL EFFECTS OF DECREASING SATURATED FAT CONTENT OF CHICKEN LIVER PÂTÉ THROUGH SUBSTITUTION WITH SUNFLOWER SEED OIL BASED OLEOGELS AND VEGETABLE PUREES : The use of oleogels in liver pâté. - SERDAROĞLU, Meltem; Karaman, Merih (Food and Feed Research, 2025)
This study investigated the impact of using oleogel made with sunflower oil and vegetable puree on the quality of chicken liver pâté. In this experiment, beef fat was partially or completely replaced with oleogels at levels of 50% (O5) and 100% (O10). Additionally, in the oleogel-enriched samples (OS5 and OS10), chicken liver was substituted with vegetable puree by 15%. All substituted groups showed a significant reduction in total fat and cholesterol content while exhibiting a significant increase in protein content. Cooking loss increased progressively with the higher substitution ratios. Additionally, the TBARS values of the oleogel-added groups were significantly lower than those of the control group by the end of the storage period.